John Conrad Waterlow. 13 June 1916—19 October 2010. (22nd December 2018) - Millward, D. Joe
Abstract : John Waterlow was an inspiring clinical and laboratory-based nutritional scientist, who was recognized as paterfamilias of a large, international and influential group of distinguished acolytes. His early work was characterized by study of the nature and clinical management of infantile malnutrition, notably as director of the MRC's Tropical Metabolism Research Unit, which he established in Jamaica in 1954. His London period, from 1970 until and beyond his official retirement in 1982, involved him as Head of the Nutrition Department at the London School of Hygiene & Tropical Medicine. Here he established a Clinical Nutrition and Metabolism Unit to continue his experimental animal and human studies researching protein metabolism; he also assumed the role of the the UK's most influential public health nutritionist, becoming President of the Nutrition Society. Like all great scientists, his work encompassed a very wide range of scientific disciplines, although he modestly described himself as a physiologist, consistent with his primary Cambridge training. Above all, throughout his career, he was happiest as an experimentalist at the bench, from his first assignment studying heat stroke of British troops in the Iraq desert during the Second World War to his measurement of [ 15 N] enrichment in urea as part of his study of whole-body protein turnover just prior to his retirement, working with an isotope ratio mass spectrometer which, like much of the equipment he used, he had largely assembled himself.